Aluminum electrolysis cell anti-permeation castable taking ferrotitanium slag as raw material as well as preparation method and use method of aluminum electrolysis cell anti-permeation castable

By using materials such as titanium slag aggregate and prefabricated fine powder, an aluminum electrolytic cell anti-permeability castable with high permeability is prepared, which solves the problem of insufficient erosion-resistant penetration ability in the prior art and achieves higher chemistry Stability and mechanical strength and reduce production costs.

CN119462097AActive Publication Date: 2025-02-18WUHAN UNIV OF SCI & TECH +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411566461.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-18
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

When the existing aluminum electrolytic tank anti-seepage castable material faces aluminum liquid corrosion and electrolyte penetration conditions, it has insufficient erosion-resistant penetration ability, especially weaker penetration resistance to elements such as Na+ and F-.

Method used

Using titanium slag as raw material, calcination and crushing obtain titanium slag aggregate and pre-made fine powder. Combined with calcium aluminate cement and sodium tripolyphosphate and other materials, an aluminum electrolytic cell anti-permeability castable is prepared with high penetration resistance. .

Benefits of technology

The corrosion-resistant penetration ability, chemical stability and mechanical strength of the anti-permeability castable in aluminum electrolyte cells is improved, especially the penetration resistance of elements such as Na+ and F-, which delays the penetration of electrolytes and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462097A_ABST
    Figure CN119462097A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of refractory materials, in particular to an aluminum electrolysis cell impermeable castable with ferrotitanium slag as a raw material and a preparation method and a use method of the aluminum electrolysis cell impermeable castable. The invention relates to an aluminum electrolysis cell impermeable castable taking ferrotitanium slag as a raw material. The aluminum electrolysis cell impermeable castable comprises the following raw materials in parts by mass: 50-55 parts of ferrotitanium slag aggregate; 40 to 45 parts of prefabricated fine powder; 3-4 parts of a binding agent; 0.15 to 0.18 part of a water reducing agent; the prefabricated fine powder comprises crushed powder, third-grade alumina fine powder, flint clay fine powder and silica powder; wherein a preparation method of the crushed powder comprises the following steps: placing a titanium-iron slag block body on a cushion sand layer paved by titanium-iron slag particles, calcining under an air atmosphere condition, cooling, taking the cushion sand layer, and crushing to obtain the crushed powder. The prepared aluminum electrolysis cell anti-permeation castable with the ferrotitanium slag as the raw material has the advantages of being good in erosion and permeation resistance, high in chemical stability and high in mechanical strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of refractory materials, and in particular to an anti-permeability castable for an aluminum electrolytic cell using ferrotitanium slag as a raw material, and a preparation method and a use method thereof. Background Art

[0002] Aluminum electrolytic cells are key equipment for the preparation of aluminum in modern industry. Since there are masonry gaps in the working layer, aluminum liquid can easily penetrate and react with refractory materials. Therefore, anti-permeability castables are required between the carbon bricks on the side walls and the insulation layer to prevent the penetration of aluminum liquid and electrolytes such as cryolite. The anti-permeability castables currently used for aluminum electrolytic cells are mainly aluminum silicate castables. However, when faced with aluminum liquid corrosion and electrolyte penetration conditions, there is still a serious problem of corrosion and penetration.

[0003] In the prior art, Huang Kai et al. added BaSO 4 Dewetting agents improve the material's ability to resist aluminum liquid penetration. However, this method relies too much on analytically pure raw materials and is difficult to use when using industrial-grade BaSO 4 When the material is oxidized, the corrosion resistance will deteriorate, which is not conducive to large-scale industrial production (Huang Kai et al. Effect of microporization on the performance of anti-seepage castables for aluminum smelting furnaces [J]. Refractory Materials, 2013, 47 (1): 286-288.). The patented technology of "An anti-seepage castable for aluminum smelting furnace and preparation method" (CN109400188A) forms a liquid protective layer to block aluminum erosion through the reaction of potassium feldspar powder, potassium hydrogen phosphate powder and coke aggregate, but it does not improve the corrosion resistance of the aggregate itself. Summary of the invention

[0004] The purpose of the present invention is to provide an aluminum electrolysis cell anti-permeability castable with ferrotitanium slag as raw material, which has simple process, low production cost and is environmentally friendly, and a preparation method and use method thereof. The prepared aluminum electrolysis cell anti-permeability castable with ferrotitanium slag as raw material has the characteristics of good corrosion resistance, high chemical stability and high mechanical strength, especially for Na + 、F - It has strong resistance to penetration by other elements.

[0005] The invention discloses an anti-permeability castable for an aluminum electrolytic cell using titanium ferro slag as raw material, comprising the following raw materials in parts by weight: 50 to 55 parts of titanium ferro slag aggregate; 40 to 45 parts of prefabricated fine powder; 3 to 4 parts of a binder; and 0.15 to 0.18 parts of a water reducing agent.

[0006] The prefabricated fine powder includes crushed powder, tertiary alumina fine powder, coke gemstone fine powder and silicon micropowder;

[0007] The preparation method of the crushed powder is as follows: placing a ferro-titanium slag block on a sand cushion layer made of ferro-titanium slag particles, calcining it in an air atmosphere and then cooling it, and crushing the sand cushion layer to obtain crushed powder.

[0008] Furthermore, the mass fractions of each raw material in the prefabricated fine powder are as follows:

[0009] 26-30 parts of crushed powder, 30-40 parts of tertiary alumina fine powder, 20-30 parts of coke gemstone fine powder, and 10-14 parts of silicon micropowder.

[0010] Furthermore, the particle size of the prefabricated fine powder is ≤74 μm.

[0011] Furthermore, in the preparation method of the crushed powder, the calcination temperature is 1560-1620° C., and the calcination time is 4-6 hours.

[0012] Furthermore, in the method for preparing the crushed powder, the diameter of the ferrotitanium slag block is 200-300 mm, the particle size of the ferrotitanium slag particles is 8-15 mm, and the mass ratio of the ferrotitanium slag block to the ferrotitanium slag particles is 8-9:1.

[0013] Furthermore, the chemical composition of the titanium ferro slag aggregate, titanium ferro slag block and titanium ferro slag particles is 2 O 3 ≥75wt%, CaO≥10wt%, TiO 2 ≥10wt%, MgO≤2wt%, Fe 2 O 3 ≤1wt%SiO 2 ≤0.5wt%.

[0014] Furthermore, the particle size range of the ferro-titanium slag aggregate is 0.088-1 mm, 1-3 mm, and 3-5 mm, and the mass ratio thereof is (40-45):(45-50):(10-13).

[0015] Furthermore, the binder is Al 2 O 3 The calcium aluminate cement has a content of 68-71wt%, and the water reducing agent is sodium tripolyphosphate.

[0016] A method for preparing an anti-permeability castable for an aluminum electrolytic cell using ferrotitanium slag as a raw material as described above comprises the following steps:

[0017] S1. Placing the ferro-titanium slag block on a sand bed formed by ferro-titanium slag particles, calcining in an air atmosphere and then cooling, and crushing the sand bed to obtain crushed powder;

[0018] S2, ball-milling the crushed powder, the tertiary alumina fine powder, the coke gemstone fine powder and the silicon micropowder to obtain a pre-made fine powder;

[0019] S3, adding the prefabricated fine powder, ferrotitanium slag aggregate, binder and water reducing agent into a mixer in proportion and dry mixing them to obtain an anti-permeability castable for an aluminum electrolytic cell made of ferrotitanium slag.

[0020] A method for using an anti-permeability castable for an aluminum electrolytic cell using ferro-titanium slag as a raw material, comprising uniformly mixing the anti-permeability castable for an aluminum electrolytic cell using ferro-titanium slag as a raw material with water to obtain a slurry, placing the slurry in a mold for vibration molding, and performing curing, demoulding, and drying.

[0021] The mass ratio of the anti-permeability castable of the aluminum electrolytic cell using titanium iron slag as raw material to water is 100:7-8;

[0022] The curing time is 24 to 48 hours, and the curing temperature is room temperature;

[0023] The drying step is performed for 20 to 28 hours at a temperature of 110 to 115°C.

[0024] Due to the adoption of the above technical solution, the present invention has the following positive effects compared with the prior art:

[0025] 1. Ca(Al,Ti) with complete and dense crystal structure in ferro-titanium slag aggregate 12 O 19 Compared with the structure of calcium hexaaluminate synthesized by ordinary sintering method, the structure of staggered distribution of small crystals has better anti-penetration ability. The present invention uses the dense Ca(Al,Ti) 12 O 19 The crystals improve the penetration resistance of the refractory material prepared by the castable and enhance the aggregate's resistance to aluminum liquid corrosion. The calcium aluminate titanate crystals react with the electrolyte (cryolite) melt that penetrates into the refractory material at the interface, forming a dense titanium oxide protective layer at the boundary to prevent the electrolyte from corroding the interior of the aggregate. It can effectively change the penetration path of the cryolite melt and thus delay the penetration, thereby improving the electrolyte penetration resistance of the anti-permeability castable for aluminum electrolytic cells using titanium iron slag as raw material, while also maintaining a relatively high mechanical strength.

[0026] 2. The present invention utilizes the cushion sand layer discarded during the phase separation process of ferro-titanium slag to prepare a prefabricated powder that is easy to undergo a matrix reaction, and reacts with the electrolyte (cryolite) melt that penetrates into the interior of the refractory material to form a feldspar phase, thereby increasing the viscosity of the refractory material reaction layer melt during the erosion and penetration process, thereby weakening its ability to continue to penetrate into the interior of the refractory material, thereby improving the material's resistance to electrolyte penetration while utilizing waste.

[0027] 3. The anti-permeability castable for aluminum electrolytic cell prepared by the present invention using titanium iron slag as raw material has the characteristics of good corrosion resistance and penetration resistance, high chemical stability and high mechanical strength;

[0028] The anti-permeability castable material for aluminum electrolytic cell prepared by the present invention with titanium iron slag as raw material is tested to have a cold compressive strength of 72-80 MPa, a cold flexural strength of 9-10 MPa, and a bulk density of 2.45-2.65 g / cm 3 After 3 hours of corrosion test with cryolite melt with a molecular ratio of 2.2 at 950℃, the thickness of the discoloration layer was less than 2mm.

[0029] 4. The present invention uses the slag produced by smelting titanium-iron alloy as the main material, which significantly reduces the production cost of the anti-permeability castable for aluminum electrolytic cell using titanium-iron slag as the raw material; the present invention has a simple process, low production cost and is environmentally friendly. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 SEM-EDS image of sample 1 prepared in Example 1 after the cryolite melt erosion experiment. DETAILED DESCRIPTION

[0031] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0032] The preparation method of prefabricated fine powder is as follows:

[0033] Step 1, according to the mass ratio of ferrotitanium slag block: ferrotitanium slag particles of 8:1, place the ferrotitanium slag block with a diameter of 200-300 mm on a sand bed formed by ferrotitanium slag particles with a particle size range of 8-15 mm, calcine for 5 hours in an air atmosphere at 1600°C, cool, and crush the sand bed to obtain crushed powder.

[0034] Step 2: Take the crushed powder, put 30 parts of the crushed powder, 35 parts of the third-grade alumina fine powder, 25 parts of the coke gemstone fine powder, and 10 parts of silicon powder into a ball mill, and ball-mill to a particle size of ≤74 μm to obtain prefabricated fine powder.

[0035] Example 1

[0036] 40 parts of the above-prepared prefabricated fine powder, 55 parts of ferrotitanium slag aggregate, 3 parts of binder, and 0.15 parts of water reducer were added to a mixer for dry mixing, and 7% of the weight of the above-mentioned powder was added for mixing again.

[0037] The mixed slurry was placed in a mold for vibration molding, cured at room temperature for 48 hours, demolded, and dried at 115°C for 28 hours to obtain sample 1.

[0038] Among them, the particle size ranges of ferrotitanium slag aggregate are 0.088-1mm, 1-3mm, and 3-5mm, and the mass ratio is 40:45:10.

[0039] The binder is Al 2 O 3The content of calcium aluminate cement is 70wt%, and the water reducing agent is sodium tripolyphosphate.

[0040] After testing: cold compressive strength is 76MPa; cold flexural strength is 9MPa; bulk density is 2.52g / cm 3 After 3 hours of corrosion test with cryolite melt with a molecular ratio of 2.2 at 950℃, the thickness of the discoloration layer was less than 2mm.

[0041] Figure 1 This is a SEM-EDS image of sample 1 prepared in Example 1 after the cryolite melt erosion experiment. From the figure, we can see that the dense calcium aluminate titanate crystals have a strong influence on the F - and Na + The element penetration plays a good role in blocking the titanium element. + A protective oxide layer forms at the permeation boundary, preventing further reaction.

[0042] Example 2

[0043] 45 parts of prefabricated fine powder, 50 parts of ferro-titanium slag aggregate, 4 parts of binder, and 0.18 parts of water reducer were added to a mixer for dry mixing, and 7% of the weight of the powder was added for mixing again. Other process parameters were the same as those in Example 1 to prepare Sample 2.

[0044] After testing: cold compressive strength is 79MPa; cold flexural strength is 10MPa; volume density is 2.65g / cm 3 After 3 hours of corrosion test with cryolite melt with a molecular ratio of 2.2 at 950℃, the thickness of the discoloration layer was less than 2mm.

[0045] Example 3

[0046] 43 parts of prefabricated fine powder, 52 parts of ferrotitanium slag aggregate, 4 parts of binder, and 0.16 parts of water reducer were added to a mixer for dry mixing, and 8% of the weight of the above powder was added for mixing again. Other process parameters were the same as those in Example 1 to prepare Sample 3.

[0047] After testing: cold compressive strength is 72MPa; cold flexural strength is 9MPa; volume density is 2.49g / cm 3 After 3 hours of corrosion test with cryolite melt with a molecular ratio of 2.2 at 950℃, the thickness of the discoloration layer was less than 2mm.

[0048] For matters not mentioned above, the prior art applies.

[0049] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. An anti-permeability castable for aluminum electrolysis cell using ferrotitanium slag as raw material, characterized in that: The raw materials include the following parts by weight: 50-55 parts of ferro-titanium slag aggregate; 40-45 parts of prefabricated fine powder; 3-4 parts of binder; 0.15-0.18 parts of water reducing agent; The prefabricated fine powder includes crushed powder, tertiary alumina fine powder, coke gemstone fine powder and silicon micropowder; The preparation method of the crushed powder is as follows: placing a ferro-titanium slag block on a sand cushion layer made of ferro-titanium slag particles, calcining it in an air atmosphere and then cooling it, and crushing the sand cushion layer to obtain crushed powder.

2. The anti-permeability castable for aluminum electrolysis cell using ferrotitanium slag as raw material according to claim 1, characterized in that: The mass fractions of each raw material in the prefabricated fine powder are as follows: 26-30 parts of crushed powder, 30-40 parts of tertiary alumina fine powder, 20-30 parts of coke gemstone fine powder, and 10-14 parts of silicon micropowder.

3. The anti-permeability castable for aluminum electrolysis cell using ferrotitanium slag as raw material according to claim 1, characterized in that: The particle size of the prefabricated fine powder is ≤74 μm.

4. The anti-permeability castable for aluminum electrolysis cell using ferrotitanium slag as raw material according to claim 1, characterized in that: In the preparation method of the crushed powder, the calcination temperature is 1560-1620° C. and the calcination time is 4-6 hours.

5. The anti-permeability castable for aluminum electrolysis cell using ferrotitanium slag as raw material according to claim 1, characterized in that: In the method for preparing the crushed powder, the diameter of the ferrotitanium slag block is 200-300 mm, the particle size of the ferrotitanium slag particles is 8-15 mm, and the mass ratio of the ferrotitanium slag block to the ferrotitanium slag particles is 8-9:

1.

6. The anti-permeability castable for aluminum electrolysis cell using ferrotitanium slag as raw material according to claim 1, characterized in that: The chemical compositions of the ferro-titanium slag aggregate, ferro-titanium slag block and ferro-titanium slag particles include Al2O3≥75wt%, CaO≥10wt%, TiO2≥10wt%, MgO≤2wt%, Fe2O3≤1wt%, and SiO2≤0.5wt%.

7. The anti-permeability castable for aluminum electrolysis cell using ferrotitanium slag as raw material according to claim 1, characterized in that: The particle size of the titanium ferro slag aggregate ranges from 0.088 to 1 mm, 1 to 3 mm, and 3 to 5 mm, and the mass ratio thereof is (40 to 45): (45 to 50): (10 to 13).

8. The anti-permeability castable for aluminum electrolysis cell using ferrotitanium slag as raw material according to claim 1, characterized in that: The binder is calcium aluminate cement with an Al2O3 content of 68-71wt%, and the water reducer is sodium tripolyphosphate.

9. A method for preparing an anti-permeability castable for an aluminum electrolytic cell using ferrotitanium slag as a raw material according to any one of claims 1 to 8, characterized in that: The steps include: S1. Placing the ferro-titanium slag block on a sand bed formed by ferro-titanium slag particles, calcining in an air atmosphere and then cooling, and crushing the sand bed to obtain crushed powder; S2, ball-grinding the crushed powder, the tertiary alumina fine powder, the coke gemstone fine powder, and the silicon micropowder to obtain a pre-made fine powder; S3, adding the prefabricated fine powder, ferrotitanium slag aggregate, binder and water reducing agent into a mixer in proportion and dry mixing to obtain an anti-permeability castable for an aluminum electrolytic cell made of ferrotitanium slag.

10. A method for using an anti-permeability castable for an aluminum electrolytic cell using ferrotitanium slag as raw material, characterized in that: The anti-permeability castable for aluminum electrolysis cell using titanium ferro slag as raw material as claimed in any one of claims 1 to 8 is mixed evenly with water to obtain slurry, the slurry is placed in a mold for vibration molding, and then subjected to curing, demoulding and drying; The mass ratio of the anti-permeability castable of the aluminum electrolytic cell using titanium iron slag as raw material to water is 100:7-8; The curing time is 24 to 48 hours, and the curing temperature is room temperature; The drying step is performed for 20 to 28 hours at a temperature of 110 to 115°C.

Citation Information

Patent Citations

  • Impervious castable for aluminum melting furnace and preparation method

    CN109400188A

  • Blast furnace slag runner castable prepared from ferrotitanium slag

    CN104478448A

  • Ladle bottom castable and preparation method thereof

    CN104926325A

  • Titanium calcium aluminate castable with middle wrap and permanent layer and preparation method thereof

    CN106365660A

  • Chromite-roasting rotary kiln operation layer pouring material and preparation method thereof

    CN106747363A